The contingency and mediation relationships among internal capabilities, external partnerships, and service variety in manufacturing enterprises. (20th April 2023) - Wang, Jian; Sun, Yike; Wu, Xiaoyu; Gao, Jie
Service variety (SV) is increasing with the changing customer requirements, and how to support it may be impacted by the internal and external factors of manufacturing firms, i.e., three types of internal capabilities in design, manufacturing, and marketing; two types of external partnerships (EP), with suppliers and customers. How these factors impact SV is important for the strategy formulation of service operations. Two hypotheses are proposed and tested with empirical research on the matching relationships among SV, internal capabilities, and EP. Structural equation modelling (SEM) and qualitative comparative analysis (QCA) were adopted for examining the configurations among the above factors. The results suggested the EP play an important mediation role between internal capabilities and SV. Three kinds of configuration between internal capabilities and EP during SV were identified, i.e., R&D oriented, manufacturing oriented, and market oriented. At last, suggestions were proposed on the formulation and implementation of service operations strategy.